The California Linkages Program: Doorway to Housing Support for Child Welfare‐Involved Parents. Issue 1 (3rd November 2016) - D'Andrade, Amy; Simon, James David; Fabella, Danna; Castillo, Lolita; Mejia, Cesar; Shuster, David
Abstract: Housing instability can complicate parents' efforts to provide for their children. Child welfare service agencies have had difficulty adequately serving parents' housing needs due to limited and constrained funding streams. This article integrates the voices of four important stakeholders to illuminate how an innovative model of service system coordination called Linkages addresses housing needs for child welfare‐involved parents eligible for public assistance. Facilitated by Linkages, these parents can receive supportive housing services through programs affiliated with the California public assistance program CalWORKs. Personal narratives reflecting the diverse perspectives of stakeholders in the Linkages collaboration—the statewide program director, a child welfare services coordinator, a CalWORKs caseworker, and a parent program participant—shed light on how the collaboration assists parents in attaining case plan goals, and highlights some of the factors facilitating and hindering effective collaboration between the agencies involved. Stakeholders emphasized the value of flexible service approaches, the intensity of the efforts required, the role of advocacy, and the importance of a shared vision between agencies working together to provide housing supports.